Emotional alterations in idiopathic Parkinson's disease without dementia (2017)
Currently Parkinson’s disease (PD) is no longer considered a disease exclusively motor type, now PD is characterized as cognitive neurobehavioral pathology often results in patients emotional disturbances that degrade their quality of life. This article intended to show an updated review of the affective disorders/emotional as depression, anxiety and apathy significantly affecting physical function, psychological, individual and family of sufferers of PD. It was found that the prefrontal cortex, hippocampus, anterior cingulate cortex, limbic system and thalamic nuclei are related to depression, such as frequent psychopathological disorder in PD, also dysfunctions in the putamen, dopamine and norepinephrine are associated with emotional disturbances that characterize to anxiety or psychosocial stress states. Next, the deregulation of fronto circuits-subcortical and frontal lobe dysfunction with loss of connections to the basal ganglia, lead to generate in subjects with PD a state of discouragement to many tasks (Apathy). The results suggest that the implementation of new lines of research and intervention to detect emotional disorders in PD, with the aim of generating strategies to help improve the quality of life in patients diagnosed with PD.